Pengaruh Model Flipped Problem-based Learning berbasis Etnokimia terhadap Literasi Kimia Siswa pada Materi Larutan Penyangga - Meliana Fajri Nurkhasanah; Eli Rohaeti (Postgraduate, University of Mataram, 2026)
This study investigates the effect of an ethnochemistry-based flipped problem-based learning (FPBL) model on students’ chemical literacy in buffer solution material. The research employed a quasi-experimental design with pre-test and post-test control groups. Data were collected through chemical literacy tests and analyzed using MANOVA at a 5% significance level. The results revealed a significant difference in chemical literacy between students who learned through the ethnochemistry-based FPBL model and those instructed using a conventional scientific approach. The model contributed 23.5% to the improvement in students’ chemical literacy, indicating a substantial effect. Furthermore, students exposed to the ethnochemistry-based FPBL model demonstrated enhanced ability to integrate chemical concepts with problem-solving and apply knowledge in practical scenarios. These findings highlight the effectiveness of incorporating ethnochemistry elements into flipped problem-based learning, providing a structured and culturally relevant approach that promotes deeper understanding of chemistry concepts. This study offers evidence that the ethnochemistry-based FPBL model can serve as an effective pedagogical strategy to enhance chemical literacy, suggesting its potential for broader application in chemistry education.